The Determinants of FDI Location Choice in Indonesia - , Desyana Wati Puji Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the determinants of FDI location choice by using firm level data of 8,010 foreign firms in Indonesia during the period 2001-2009. This study divided FDI business fields into 3 sectors, which are the primary sector, the secondary sector, and the tertiary sector. Using conditional logit estimation, this study found that in the primary sector, regional GDP growth, infrastructure, and labor quality play a significant role. But, surprisingly, regional GDP growth and labor quality show a negative significant role, which is in contrast to the existing literature. In the secondary sector, infrastructure and labor quality play a positive significant role and real minimum wage plays a negative significant role, while in the tertary sector, regional GDP growth shows a positive significant role in deciding FDI location. For in all sectors, these findings suggest that the probability of a region will be selected by an investor is affected by the regional GDP growth, infrastructure condition, labor quality, and real minimum wage of a region.